INCREASING CUSTOMER STATISFACTION THROUGH IMPROVING SERVICE QUALITY AT THE PURWOREJO POST OFFICE 54100 - Pepi Zulvia; Niko Dwi Haryanto (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2021)
The level of intense business competition makes a company must continue to be able to increase customer satisfaction, then the company is required to be able to meet the needs and desires of customers, when the company is unable to increase satisfaction later, competitors may seize the customer. This study uses CSI, IPA and PGCV methods to analyze the level of satisfaction, map service quality in quadrants and determine the order of priority for improving service quality at the Purworejo Post Office 54100 The research was conducted on 52 customers using the Accidental Sampling technique. The level of satisfaction through CSI was obtained at 80.6%. Through IPA obtained 8 indicators that are included in quadrant 1 and 5 indicators included in quadrant 3. From quadrant 1 and quadrant 3 obtained the top 5 rankings through PGCV, namely 1) Fast and responsive service, 2) Response to suggestions and complaints, 3) Providing information that is easy to understand, 4) Security from any loss or damage to goods that occurs and 5) Service procedures that are not confusing. It is concluded that the Purworejo 54100 POS office still needs to make improvements in service quality to the 5 indicators in order of priority.